ELEMEN ESTETIS RUMAH PERANAKAN JAMBLANG SEBAGAI RUANG EDUKASI SEJARAH DAN BUDAYA - Krismanto Kusbiantoro; Tessa Eka Darmayanti; Elliati Djakaria; Latifah Nur Azizah; Fellicia Lodhita (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2022)
Aesthetic elements are frequently viewed as embellishments that can affect perception, thereby enriching the quality of a building or space. Aesthetic elements are also closely related to the course of history and culture, therefore this article aims to introduce history and culture through the presence of aesthetic elements in a Peranakan house in Jamblang, Cirebon. Based on this, data collection techniques are needed through direct observation, in-depth interviews, and literature exploration. This qualitative research is also supported by a phenomenological approach because the concept is related to culture, space, and perception. The findings of this study reveal that the introduction of history and culture can be done by